Role of Cu and Sr in Improving the Electrochemical Performance of Cobalt-Free Pr1-xSrxFe1-yCuyO3-δ Cathode for Intermediate Temperature Solid Oxide Fuel Cells. Issue 2 (1st January 2016) - Lu, Jun; Yin, Yi-Mei; Yin, Jiewei; Li, Jingcheng; Zhao, Jun; Ma, Zi-Feng
Abstract : The influence of Sr and Cu variation on the electrochemical performance of cobalt-free cathodes Pr1- x Sr x Fe0.8 Cu0.2 O3- δ (PSFC x, 0 ≤ x ≤ 0.5) and Pr0.5 Sr0.5 Fe1- y Cu y O3- δ (PSFC y, 0 ≤ y ≤ 0.3) for intermediate temperature solid oxide fuel cells (IT-SOFCs) was investigated in half cells and full cells. The intrinsic reasons for the improvement are revealed from the aspects of the symmetry of crystal structure, the generation and migration of oxygen vacancy in the lattice and at the surface, thermal expansion compatibility, and electrical conductivity of these materials. The unit cell symmetry enhancement, the increment of oxygen deficiency and lattice free volume, and the formation of Cu 3+ through the reduction of lattice Fe 4+ by Cu 2+ are considered to be responsible for the improvement of electrochemical performance. Sr and Cu substitutions show a synergistic effect on increasing unit cell symmetry, oxygen vacancy generation, electrical conductivity and electrochemical activity, while they demonstrate a competing way in the surface segregation.